Optimization of Resistance Load in 4T-Static Random-Access Memory Cell Based on Silicon Nanowire Transistor - Hashim, Yasir (American Scientific Publishers, 2018)
This study explores optimization of resistance load (R-Load) of four silicon nanowire transistor (SiNWT)-based static random-access memory (SRAM) cell. Noise margins and inflection voltage of butterfly characteristics with static power consumption of SRAM cell are used as limiting factors in this optimization. Range of R-Load used in this study was 20–1000 KΩ with V dd= 1 V. Results indicate that optimization depends critically on resistance load value. The optimized range of R-Load is 100–200 KΩ.